2014
DOI: 10.1039/c3ta14751g
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired surface-functionalization of graphene oxide for the adsorption of organic dyes and heavy metal ions with a superhigh capacity

Abstract: By utilizing the synergistic effect of poly-dopamine (PD) with functional groups and graphene oxide (GO) with a high surface area, a series of sub-nano thick PD layer coated GO (PD/GO) composites were fabricated and used for effectively decontaminating wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(132 citation statements)
references
References 62 publications
3
128
0
1
Order By: Relevance
“…Other researches have also demonstrated that GO is an ideal material for the sorption of various kinds of species due to their large surface area and a large number of functional groups on the edges and defect sites of GO [28]. For example, it is demonstrated that the organic dyestuffs can be adsorbed on GO layers mainly through a hydrogen bonding, charge attraction or -interaction between the functional groups of dyestuffs and the polar groups of GO layers, including carboxyl, hydroxyl, and epoxy groups [29][30][31]. Similarly, the presence of functional groups such as carboxyl and hydroxyl groups on the surface also make GO an additive to enhance the hydrophilicity of membranes.…”
Section: Introductionmentioning
confidence: 96%
“…Other researches have also demonstrated that GO is an ideal material for the sorption of various kinds of species due to their large surface area and a large number of functional groups on the edges and defect sites of GO [28]. For example, it is demonstrated that the organic dyestuffs can be adsorbed on GO layers mainly through a hydrogen bonding, charge attraction or -interaction between the functional groups of dyestuffs and the polar groups of GO layers, including carboxyl, hydroxyl, and epoxy groups [29][30][31]. Similarly, the presence of functional groups such as carboxyl and hydroxyl groups on the surface also make GO an additive to enhance the hydrophilicity of membranes.…”
Section: Introductionmentioning
confidence: 96%
“…However, it was found that although SG-pD carries fewer negative charges than SG in the tested pH range, conversely, it showed higher adsorption capacities than SG, which might be resulted from the fact that the adsorption process was not merely attributed to the electrostatic attraction between cationic MB and negatively charged active sites on SG-pD but the contributions of stacking and 1,4-Micheal addition reaction between MB and pD, etc. [35,38,39]. Some other results should be expounded here.…”
Section: Effect Of Phmentioning
confidence: 80%
“…The oxygen-containing groups, such as epoxy (C-O-C), hydroxyl (-OH) and carboxyl (-COOH) groups on both basal planes and edges, allowed GO to form homogeneous suspensions in water and introduced negative charges for the adsorption of positively charged heavy metal irons via electrostatic interaction [15]. For example, Romanchuk et al [16] found that the maximum sorption capacity of GO for Eu(III) and U(VI) removal were 0.76 and 0.12 mmol·g -1 , respectively.…”
Section: Introductionmentioning
confidence: 99%